Settlement of piles with negative skin friction: design approaches according to part 3 of Eurocode 7 - Alena Zemanová; Vojtěch Anderle; Jan Masopust (Acta Polytechnica)
Piles offer an effective solution for supporting structures in challenging ground conditions. However, ground settlement around deep foundations can induce negative skin friction, adding complexity to the geotechnical analysis and requiring careful consideration in both the pile settlement evaluation and structural integrity design. The article discusses the general recommendations provided by the informative annex of the revised Eurocode 7 version for designing piles subjected to negative skin friction. Using the Fellenius unified pile design concept, we provide a practical design framework for piles subjected to negative skin friction that extends the load-settlement curve methods proposed by Masopust, representing the standard pile design approaches in the Czech Republic. For examples presented, the introduced practical approach, also suitable for manual calculations, is in very good agreement with a refined calculation providing a nonlinear load-settlement curve.